Colorimetric detection of Pseudomonas aeruginosa by aptamer-functionalized gold nanoparticles - Schmitz, Fernanda Raquel Wust; Cesca, Karina; Valério, Alexsandra; de Oliveira, Débora; Hotza, Dachamir (Applied microbiology and biotechnology, 2023)
Novel rapid methodologies for the detection of bacteria have been recently investigated and applied. In hospital environments, infections by pathogens are very common and can cause serious health problems. Pseudomonas aeruginosa is one of the most common bacteria, which can grow in hospital equipment such as catheters and respirators. Even at low concentrations, it can cause severe infections as it is resistant to antibiotics and other treatments. Based on this subject’s relevance, this work aimed to develop a colorimetric biosensor using aptamer-functionalized gold nanoparticles for identifying P. aeruginosa . The detection mechanism is based on the color change of gold nanoparticles (AuNPs) from red to blue-purple through NaCl induction after bacteria incubation and aptamer-target binding. First, AuNPs were synthesized and characterized. The influence of aptamer and sodium chloride concentration on the agglomeration of AuNPs was investigated. Optimization of aptamer concentration and salt addition were performed. The best condition for detection was 5 µM aptamers and 200 mM of NaCl. In this case, P. aeruginosa was detected after 5 h for concentrations from 10 8 to 10 5 CFU mL −1 , being 10 5 and 10 4 CFU mL −1 the detection limit for color change by the naked eye and UV–Vis spectrometry, respectively. In addition, other bacteria such as E. coli , S. typhimurium , and Enterobacteriaceae bacterium were also detected with color changing from red to gray. Finally, it was confirmed that the salt incubation time can be 2 h, and that the ideal aptamer concentration is 5 µM. Thus, the colorimetric analysis can be a simple and fast detection method for P. aeruginosa in the range of 10 8 to 10 5 CFU mL −1 to the naked eye. Graphical Abstract Key Points • A new method for rapid detection of Pseudomonas aeruginosa • Aptamers conjugated with gold nanoparticles allow pathogen detection by colorimetry • No need for previous surface modification of nanoparticles